PENGARUH MINAT KONSUMEN DAN MEDIA SOSIAL TERHADAP PENGGUNAAN ALAT PEMBAYARAN NON TUNAI - Ahmad Gani, Ackhriansyah; Vandy, Al (AkMen JURNAL ILMIAH, 2023)
This research aims to determine the influence of consumer interest and social media on the use of non-cash payment instruments among UMI Faculty of Economics and Business students. This research uses quantitative data, data collection in this research uses a questionnaire containing 14 questions and distributed to 97 respondents who use non-cash payments in transactions on social media. Data analysis techniques use validity tests, reliability tests, descriptive data analysis, multiple linear regression analysis and hypothesis testing. The results of the research conducted show that consumer interest and social media simultaneously influence the use of non-cash payment instruments. Then, partially, consumer interest and social media also have a significant influence on the use of non-cash payment instruments.